Investigation on the upconversion luminescence in Ho3+/Yb3+ co-doped Ba3Sc4O9 phosphor. (February 2018) - Liu, Shuifu; Liu, Songbin; Ming, Hong; Hou, Dejian; You, Weixiong; ye, Xinyu
Graphical abstract: Highlights: The optical properties of novel Ba3 Y4 O9 :Ho 3+ /Yb 3+ phosphor were investigated. The luminescence color could be tuned from green to yellow-green light. The energy transfer mechanisms of UC luminescence were investigated in detail. The phosphor can be a good candidate for green UC material in display fields and fluorescent labeling. Abstract: A series of Ba3 Sc4 O9 :Ho 3+ /Yb 3+ phosphors were synthesized by a high-temperature solid-state reaction method. The phase purity and upconversion luminescence were characterized by X-ray diffraction and photoluminescence spectroscopy. The sintering temperature and doping concentrations were optimized to obtain the strongest emission intensity. Under 980 nm laser diode excitation, the green (545 nm, 5 F4 / 5 S2  →  5 I8 ) and red (665 nm, 5 F5  →  5 I8 ) emissions were observed. The cross-relaxation and back-energy-transfer processes play an important role to adjust the emission intensity ratio of Green/Red at different dopant concentrations. Based on the energy level diagrams, the energy transfer mechanisms are investigated in detail according to the analysis of pump power dependence and luminescence decay curves. The upconversion luminescence properties of the phosphor were evaluated and the results show good color monochromaticity and relatively high upconversion luminescence intensity. The Ba3 Sc4 O9 :Ho 3+ /Yb 3+ can be a good candidate for green upconversion material in display fields and fluorescent labeling.